The arrangement ebook - Day, Sylvia (2020)
"A well-curated selection of sexy, short, captivating romances from big-name authors investigating the unexpected twists of arranged marriages." — Library Journal A trio of sizzling historical romances that prove passion is timeless . . . Mischief and the Marquess by Sylvia Day Justin, the Marquess of Fontaine, and Lady Sophie Milton-Riley are completely ill-suited to one another. But they will have to prove it in order to end their mothers' insistence that they should marry. Yet the more they attempt to demonstrate how wrong their union would be, the more surprisingly, irresistibly right things feel . . . THE DUKE'S TREASURE by Minerva Spencer Plain, prickly Josephine Loman has loved Beaumont Halliwell, the Fifth Duke of Wroxton, since the first time she saw him. But the most beautiful man she's ever met had eyes only for Jo's erstwhile friend, who betrayed Beau's trust by marrying his brother. Beau hasn't been home in years, but when his brother dies in an accident, he must marry to save the impoverished dukedom. And Jo is the overlooked heiress who will turn his world upside down . . . THE INCONVENIENT COUNTESS by Kristin Vayden As the eldest in a poverty-stricken family of daughters, Miss Diana Katherine Lambson's only option is a marriage of convenience. Her only prospect is a rogue with a miserable reputation. Her only true desire: freedom. And that is exactly what Charles Brook, Earl of Barrington, is willing to offer, in return for the respectability their union will give him. He will even provide Diana with a contract. But does she dare entrust her future to a scoundrel? Does she dare not to?